2021
DOI: 10.3390/molecules26195919
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Bioactivity and Safety Evaluation of Ethanolic Extracts of Zanthoxylum schinifolium Fruit and Pericarp

Abstract: The fruit and pericarp of Zanthoxylum schinifolium (ZS) have been used in traditional medicine; however, few studies have characterized ZS fruit and pericarp. Therefore, in the present study, we evaluated the safety of ZS fruit (ZSF) and pericarp (ZSP) extracts and compared their bioactivity. To evaluate the safety of ZSF and ZSP, mutagenicity, cytotoxicity, and oxidative stress assays were performed and nontoxic concentration ranges were obtained. ZSP was found to be superior to ZSF in terms of its antimutage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…AGEs have an important role in the progression and pathogenesis of AD, as Aβ aggregation is accelerated in the presence of AGEs [99]. The content of AGEs is more in neurofibrillary tangles (NFTs) and plaques, as suggested by immunohistochemical studies [100]. Additionally, both ZP and ZS effectively protect human-derived neuronal cells from high glucose-induced cytotoxicity, indicating the neuroprotective nature of the plants.…”
Section: Carbazole Alkaloids From Zanthoxylummentioning
confidence: 96%
“…AGEs have an important role in the progression and pathogenesis of AD, as Aβ aggregation is accelerated in the presence of AGEs [99]. The content of AGEs is more in neurofibrillary tangles (NFTs) and plaques, as suggested by immunohistochemical studies [100]. Additionally, both ZP and ZS effectively protect human-derived neuronal cells from high glucose-induced cytotoxicity, indicating the neuroprotective nature of the plants.…”
Section: Carbazole Alkaloids From Zanthoxylummentioning
confidence: 96%
“…Various studies have compared the antioxidant activities of ascorbic acid and berry extracts. It was reported that winter cherry, Zanthoxylum schinifolium fruit, and acai berry showed antioxidant activities of 20.81% (with FRAP assay), 22.7% (with ABTS assay), and 78.8% (with DPPH assay), respectively, compared to ascorbic acid [60][61][62].…”
Section: Antioxidant Activity Assessment Of the Elderberry Extractmentioning
confidence: 99%